“Implementación de un circuito turístico para impulsar el turismo inclusivo en el cantón El Empalme, provincia del guayas, año 2021” - Guerra Rizzo, Margarita Elizabeth (2021)
This research was conducted in order to implement a tourist circuit that promotes inclusive tourism in the canton El Empalme, province of Guayas, acording to the problems presented by focusing on accessibility facilities anda travel in tourist attractions for people with disabilities, which prevents the canton to be a destination that offers and bets on inclusiveness in tourism, adding to it the pandemic by Covid – 19, the lack of interest of the highest authorities, in this research it was of utmost importance to apply investigative methods in order to give an answer to the formulation of the problem posed, thus calculating the number of people to consider when asking a series of questions in relation to the main theme, the inclusive circuit, in which a group of people with disabilities was also considered since they are the most appropriate to answer the questions. The results show that most of the attractions identified for the circuit do not have the corresponding facilities for the user with a disability, whether motor, hearing, among others, being these the most striking attractions of the canton, for its beauty, importance, history, there is no management by the authorities is order to improve them for tourism, surveys show that people are interested in traveling, in learning more about their land, and in taking into account people with disabilities, so that they can enjoy the attractions and wealth of the canton, with security, economic accesibility and other factors, for this inclusive circuits was designed and that was socialized with the citizens of empalmense for their benefit in turn developing a Full Day. In conclusion, the canton of El Empalme has everythings to be a potencial inclusive tourist destination, but without the appropriate management measures, development would not be posible, which will open new Jobs, new projects, which would bring very good benefits to the canton. Inclusive Tourism – Disability – Tourist Circuit.